Efficient Solar Light Photocatalyst Made of Ag3PO4 Coated TiO2-SiO2 Microspheres - Sudipto Pal; Sanosh Kunjalukkal Padmanabhan; Amruth Kaitheri; Mauro Epifani; Antonio Licciulli (Nanomaterials, 2023)
Solar light active photocatalyst was prepared as silver phosphate (Ag3PO4) coating on titania–silica (TiO2–SiO2) microspheres. Titania–silica microsphere was obtained by spray drying TiO2–SiO2 colloidal solutions, whereas Ag3PO4 was applied by wet impregnation. XRD on the granules and SEM analysis show that the silver phosphate particles cover the surface of the titania–silica microspheres, and UV-visible diffuse reflectance analysis highlights that Ag3PO4/TiO2–SiO2 composites can absorb the entire visible light spectrum. BET measurements show higher specific surface area of the composite samples compared to bare Ag3PO4. Photocatalytic activity was evaluated by dye degradation tests under solar light irradiation. The prepared catalysts follow a pseudo-first-order rate law for dye degradation tests under solar light irradiation. The composite catalysts with an Ag3PO4/TiO2–SiO2 ratio of 1:1.6 wt% show better catalytic activity towards both rhodamine B and methylene blue degradation and compared with the results with uncoated TiO2–SiO2 microspheres and the benchmark commercial TiO2 (Evonik-P25) as a reference. The composite photocatalyst showed exceptional efficiency compared to its pristine counterparts and reference material. This is explained as having a higher surface area with optimum light absorption capacity.